2005
DOI: 10.1063/1.1909031
|View full text |Cite
|
Sign up to set email alerts
|

Variational calculation of vibrational linear and nonlinear optical properties

Abstract: A variational approach for reliably calculating vibrational linear and nonlinear optical properties of molecules with large electrical and/or mechanical anharmonicity is introduced. This approach utilizes a self-consistent solution of the vibrational Schrödinger equation for the complete field-dependent potential-energy surface and, then, adds higher-level vibrational correlation corrections as desired. An initial application is made to static properties for three molecules of widely varying anharmonicity usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 65 publications
2
45
0
Order By: Relevance
“…Of course, the ␣ nr approximation would have a far worse performance for more anharmonic systems. 31 In addition to our results for ␣ nr we have for comparison also included the results of ␣ nr obtained by Torrent-Sucarrat et al 31 Table III show that, in complete agreement with our FVCI linear response results, when this correction is added to ␣ nr the value of the zz component of the PV polarizability increases by about 9%. Torrent-Sucarrat et al.…”
Section: Convergence With Respect To Details Of the Potential And Prosupporting
confidence: 66%
See 3 more Smart Citations
“…Of course, the ␣ nr approximation would have a far worse performance for more anharmonic systems. 31 In addition to our results for ␣ nr we have for comparison also included the results of ␣ nr obtained by Torrent-Sucarrat et al 31 Table III show that, in complete agreement with our FVCI linear response results, when this correction is added to ␣ nr the value of the zz component of the PV polarizability increases by about 9%. Torrent-Sucarrat et al.…”
Section: Convergence With Respect To Details Of the Potential And Prosupporting
confidence: 66%
“…Concerning the variation in the potential we observe that almost converged results may be obtained at the V͓2M4T͔ level. Finite field MP2/Pol FVCI calculations performed by Torrent-Sucarrat et al 31 showed that the inclusion of fifth and sixth order terms in the Taylor expansion for the potential ͑V͓3M6T͔͒ causes a decrease of 2% to the total vibrational polarizability ͑PV+ ZPVA͒. Thus, we expect that our error due to the exclusion of such fifth and sixth order terms has a similar effect.…”
Section: Convergence With Respect To Details Of the Potential And Promentioning
confidence: 59%
See 2 more Smart Citations
“…19 The ZPVA, in turn, can be obtained by applying variational procedures to solve the vibrational Schrödinger equation. 20,21 Experimental measurements are often carried out at optical frequencies much larger than the frequencies of the relevant vibrational excitations. In that event, one may invoke the infinite optical frequency approximation [22][23][24] ͑IOFA͒ in calculating vibrational NLO properties.…”
Section: Introductionmentioning
confidence: 99%